Analysis Antioxidant of Fractions Cocoa Beans (Theobroma Cacao L.) as Potential Herbal Medicine - Wibawa, Agung Ari Chandra; Pramitha, Dewa Ayu Ika; Sanjiwani, Ni Made Sukma; Adrianta, Ketut Agus (Hydrogen: Jurnal Kependidikan Kimia, 2024)
The cocoa seeds of the Gumbrih-Bali region are a natural commodity with great potential for development or processing by local communities. The purpose of this research is to provide information about the antioxidant potential contained in cocoa seeds. Testing the antioxidant capacity in this study uses the Uv-Vis spectrophotometry method at 517 nm wavelengths. Free radical scavanger is measured with control absorption and samples was analyzed with regression curve. The research results proved that the antioxidant (AAI) in the n-butanol fraction show result very strong ability of 4.64 compared to the 0.42 ethyl acetate fraction and 0.46 n-hexane fraction. These results prove that the potential chemical content of cocoa seeds is high in polar solvents (n-butanol fractions) such as flavonoid compounds. Furthermore, this research will be used as a basis for developing natural herbal ingredients such as cocoa which can be consumed in the community to prevent degenerative diseases.